Money employment and inflation - Barro, Robert J.; Grossman, Herschel I. (Cambridge ; New York : Cambridge University Press, 1976)
This is a textbook on macroeconomic theory that attempts to rework the theory of macroeconomic relations through a re-examination of their microeconomic foundations.
Includes index.
Includes bibliographical footnotes: p. 259-263.
aia 09/04/2018
Loans
Keywords: Macroeconomics